Iceland West (ICW) Super Dual Auroral Radar Network (SuperDARN) High Frequency (HF) Radar Ground Scatter Data (2023) - Evan Thomas; Simon Shepherd (Arctic Data Center, 2023)
The Super Dual Auroral Radar Network (SuperDARN) is an international network of ground-based, space weather radars which have operated continuously in the Arctic and Antarctic regions for more than 30 years. These high-frequency (HF) radars use over-the-horizon (OTH) radio wave propagation to detect ionospheric plasma structures across ranges of several thousand kilometers (km). As a byproduct of this technique, the transmitted radar signals frequently reflect from the Earth's surface and can be observed as ground backscatter echoes. The monthly files in this dataset contain maps of daily ground backscatter observations from the Iceland West (ICW) SuperDARN HF radar binned onto an equal-area 24 km grid. The ICW radar is located in Þykkvibær, Iceland (63.77°N, 20.54°W) and is operated by Dartmouth College (Principal Investigator: Simon G. Shepherd, simon.g.shepherd@dartmouth.edu) with funding support from the National Science Foundation.